Modeling Frequency Reduction in Human Groups Performing a Joint Oscillatory Task - Calabrese, Carmela; Bardy, Benoît G.; De Lellis, Pietro; di Bernardo, Mario (Frontiers in Psychology, 2022)
In human groups performing oscillatory tasks, it has been observed that the frequency of participants' oscillations reduces when compared to that acquired in solo. This experimental observation is not captured by the standard Kuramoto oscillators, often employed to model human synchronization. In this letter, we aim at capturing this observed phenomenon by proposing three alternative modifications of the standard Kuramoto model that are based on three different biologically-relevant hypotheses underlying group synchronization. The three models are tuned, validated and compared against experiments on a group synchronization task, which is a multi-agent extension of the so-called mirror game.